The water quality of the Ria de Aveiro lagoon, Portugal: from the observations to the implementation of a numerical model - Lopes, J. F.
Ria de Aveiro is a very important area of the Portuguese coast, which has been under an increasing anthropogenic pressure for several decades and, contributes to the degradation of the lagoon’s water quality. This work presents both a characterisation of the water quality of the Ria de Aveiro lagoon, using physical, chemical and biological experimental data, and an implementation of a numerical model for the water quality of the lagoon. The ultimate goal is to obtain an accurate numerical model able to simulate major water quality features of the lagoon under the influence of different forcing conditions. Data analysis reveals good correlations between the salinity and almost all the water quality variables as well as between the different variables. The maximum biochemical oxygen demand concentration (BOD) depends on the light intensity, the temperature and the river inputs. The main vulnerable areas of the lagoon, from the water quality point of view, seem to be the far end of the main channels, where low dissolved oxygen concentration (DO) and high BOD concentrations are observed. The numerical model of the Ria de Aveiro has reproduced both winter–spring and spring–summer events related to the lagoon water quality as well as its main pattern. Both data and modelling results show that the BOD5 concentrations (where the subscript ‘5’ means that the BOD measurements were conducted for five days, without inhibitor of nitrification) are driven by the river influence, during the winter–spring period, and by the biological activity during the spring–summer period. The DO concentrations show high values in the spring–summer period and smaller concentrations in the winter–spring period at the far end of the lagoon. The application of the model to the study of scenarios has demonstrated the role of nutrients and light in the phytoplankton growth, the relationship between DO and phytoplankton concentrations, as well as the effect of the BOD degradation in the ammonia (NH4) regeneration.